1990
DOI: 10.2466/pms.1990.71.3.963
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Boredom Proneness Scale

Abstract: A factor analysis of the data from 154 subjects answering Farmer and Sundberg's (1986) boredom proneness scale allowed estimates of reliability and construct validity and the identification of two independent factors, apathy and inattention. Correlations of these factors and the total test scores were made with measures of extraversion and depression and the scores on a simple repetitive task. The results suggest that boredom is associated with extroversion and depression, and that this association is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 5 publications
6
67
0
3
Order By: Relevance
“…Originally considered a unitary construct, the psychometric properties and underlying factor structure of the BPS soon became the subject of intense scrutiny, not only in the United States where it was first developed (Vodanovich and Kass, 1990a;Vodanovich et al, 1997;Vodanovich et al, 2005;Melton and Schulenberg, 2009) but in Canada (Ahmed, 1990), Australia (Gordon et al, 1997), France (Gana and Akremi, 1998) and Turkey (Dursun and Tezer, 2013).…”
Section: A Trait To Be Measuredmentioning
confidence: 99%
“…Originally considered a unitary construct, the psychometric properties and underlying factor structure of the BPS soon became the subject of intense scrutiny, not only in the United States where it was first developed (Vodanovich and Kass, 1990a;Vodanovich et al, 1997;Vodanovich et al, 2005;Melton and Schulenberg, 2009) but in Canada (Ahmed, 1990), Australia (Gordon et al, 1997), France (Gana and Akremi, 1998) and Turkey (Dursun and Tezer, 2013).…”
Section: A Trait To Be Measuredmentioning
confidence: 99%
“…However, the Boredom Proneness Scale (BPS; Farmer & Sundberg, 1986), the most commonly used measure of trait boredom proneness, has been shown to be multifactorial (Vodanovich & Kass, 1990;Ahmed, 1990). Although there is some disagreement as to the number of factors needed to fully capture the variance in the BPS, a review by Vodanovich and colleagues (2005) suggested that the BPS can be consistently divided into at least two factors -boredom proneness originating from a perceived lack of external stimulation (external factor) and boredom proneness originating from a perceived lack of internal stimulation (internal factor).…”
Section: Boredom Is Not a Unitary Constructmentioning
confidence: 99%
“…The internal consistency of the original BPS has showed by a lot of authors such as Ahmed (1990), Blunt & Pychyl (1998), Gana & Akremi (1998). However, the form used in this study was the 7-point Likert that has yielded coefficient alphas from 0.79 to 0.84 across numerous studies (Vodanovich, Wallace, & Kass, 2005;Harris, 2000;Seib & Vodanovich, 1998;Wink & Donahue, 1997); the authors have employed this modification of the instrument to increase the sensitivity of measurement.…”
Section: Methodsmentioning
confidence: 99%